Penggunaan Aplikasi Canva Untuk Membuat Konten Gambar pada Media Sosial Sebagai Upaya Hasil Produk UMKM di Desa Kebun Durian Kabupaten Kampar - Antoni Pribadi; Andri Nofiar, Am; Indah Purnama Putri; Rahmad Akbar; Dzulhijjah Yetti; Ardiansyah Hamid; Merlia Rahma Yani; Nofrifaldi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Currently, MSME stakeholders are facing problems in selling their products as they often focus too much on the production process and do not balance marketing and advertising. When a product is produced in large quantities, it becomes difficult to sell quickly. Advertising is usually done by word of mouth or by displaying products in local stores. Efforts to overcome MSME marketing include providing training to his MSME stakeholders through digitization. Digitization of MSME is an attempt by an MSME subject to digitize the marketing of his MSME products. Simply put, it makes it easier for business people to sell their products online in an increasingly demanding technology age. One of his ways to digitize MSME product marketing is with the Canva application. Canva is an online design program that offers video, image or photo editing, graphic design and more. The service activities conducted are intended to provide insight into the use of social media by MSMEs in conducting promotions and creating engaging and easy-to-implement product content. Training will also be provided to MSMEs in Kebun Durian Village to utilize the results of MSMEs in promoting digital technology. Up to 34 trainees were able to create mockups and logo designs using his Canva application as an advertising medium to increase the sales value of their MSME products.